Superhydrophobic surfaces via controlling the morphology of ZnO micro/nano complex structure - 公茂刚 许小亮 杨周 刘艳松 刘玲 (Chinese physics B, 2010)
ZnO micro/nano complex structure films, including reticulate papillary nodes, petal-like and flake-hole, have been self-assembled by a hydrothermal technique at different temperatures without metal catalysts. The wettability of the above film surfaces was modified with a simple coating of heptadecafluorodecyltrimethoxy-silane in toluene. After modifying, the surface of ZnO film grown at 50℃ was converted from superhydrophilic with a water contact angle lower than 5° to superhydrophobic with a water contact angle of 165° Additionally, the surface of reticulate papillary nodes ZnO film grown at 100 ℃ had excellent superhydrophobicity, with a water contact angle of 173° and a sliding angle lower than 2° Furthermore, the water contact angle on the surface of petal-like and flake-hole ZnO films grown at 150℃ and 200℃ were found to be 140° and 120°, respectively. The wettability for the samples was found to depend strongly on the surface morphology which results from the growth temperature.